A comparison of serotonin neuromodulation of mouse spinal V2a interneurons using perforated patch and whole cell recording techniques - Dietz, Shelby B.; Husch, Andreas; Harris-Warrick, Ronald M. (Frontiers in Cellular Neuroscience, 2012)
Whole cell recordings (WCRs) are frequently used to study neuronal properties, but may be problematic when studying neuromodulatory responses, due to dialysis of the cell’s cytoplasm. Perforated patch recordings (PPR) avoid cellular dialysis and might reveal additional modulatory effects that are lost during WCR. We have previously used WCR to characterize the responses of the V2a class of Chx10-expressing neurons to serotonin (5-HT) in the neonatal mouse spinal cord (Zhong et al. 2010). Here we directly compare multiple aspects of the responses to 5-HT using WCR and PPR in Chx10-eCFP neurons in spinal cord slices from 2-4 day old mice. Cellular properties recorded in PPR and WCR were similar, but PPR cells remained healthy for significantly longer. Both WCR and PPR cells could respond to 5-HT, and although neurons recorded by PPR showed a significantly greater response to 5-HT in some parameters, the absolute differences between PPR and WCR were small. We conclude that WCR is an acceptable recording method for short-term recordings of neuromodulatory effects, but the less invasive PPR is preferable for detailed analyses and is necessary for stable recordings lasting an hour or more.